Hydrogen jet vapor cloud explosion: A model for predicting blast size and application to risk assessment. Issue 3 (24th March 2018) - Jallais, Simon; Vyazmina, Elena; Miller, Derek; Thomas, J. Kelly
Abstract : Releases of hydrogen at elevated pressures form turbulent jets in unconfined & uncongested regions may trigger vapor cloud explosion (VCE) as well as jet fire hazards. In the case of a delayed ignition of an unconfined & uncongested jet the turbulence induced by the jet release can lead to flame speeds sufficient to produce damaging blast loads, even in the absence of confinement or congestion. The VCE hazard posed by such high‐pressure hydrogen releases is not well‐recognized. The authors have previously presented test data and computational fluid dynamic (CFD) modeling analyses which characterize high pressure hydrogen releases and the associated VCE hazard in unconfined & uncongested regions. The current paper provides an overview of this VCE hazard. It presents both CFD simulations and a new simplified method. The new method determines the blast strength based on a blast curve method (i.e., TNO multienergy or BST) with the strength index correlated to the mass flow rate of the accidental release. The paper discusses also the implications of such events for building siting analyses and risk assessments. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 37:397–410, 2018